A Humean Constructivist Reading of J. S. Mill's Utilitarian Theory. Issue 2 (7th August 2015) - DRAKE, NICHOLAS
Abstract : There is a common view that the utilitarian theory of John Stuart Mill is morally realist and involves a strong kind of practical obligation. This article argues for two negative theses and a positive thesis. The negative theses are that Mill is not a moral realist and that he does not believe in certain kinds of obligations, those involving external reasons and those I call robust obligations, obligations with a particular, strong kind of practical authority. The positive thesis is that Mill's metaethical position can be interpreted as a Humean constructivist view, a metaethical view that is constructivist about value and entails the existence of practical reasons, but not external reasons or robust obligations. I argue that a Humean constructivist reading of Mill's theory is reasonable, and strengthens Mill's argument from desire for the value of happiness, an important but notoriously weak aspect of his theory.